Format-Independent Protection of DNA Microarray Images - Pizzolante, Raffaele; Castiglione, Arcangelo; Carpentieri, Bruno; De Santis, Alfredo; Palmieri, Francesco; Castiglione, Aniello (2015 10th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC), 2015)
DNA microarray images are an essential research tool in several fields, such as, forensic biology, single nucleotide polymorphism, functional analysis of genes, DNA sequencing, diagnosis of hereditary and infectious diseases, etc. Consequently, these images can be exchanged between different entities with different roles and belonging to different application domains. It is easy to note that for the reasons described above, the protection of such images, mainly in terms of authenticity and integrity is a main concern, especially in the so called multi-domain environments. It is important to remark that the use of conventional techniques for data protection, such as encryption or the adding of metadata into the image header is doomed to fail. Indeed, decrypted content may be subject to unauthorized use or manipulation, and metadata may be lost during the image processing, such as a format conversion. Therefore, in order to ensure the requirements of authenticity and integrity, it is necessary to use a security mechanism specific for DNA microarray images, which is as close as possible to such images. For this reason, in this paper we introduce a watermarking scheme explicitly designed for this kind of images. In particular, such a scheme belongs to the category of invisible reversible fragile watermarking. Finally, the validity of this scheme has been assessed through testing.